Suppression of Shastry-Sutherland phase driven by electronic concentration reduction in magnetically frustrated Ce2Pd2Sn1−yIny alloys - Sereni, Julian Gustavo Renzo (2019)
Exploiting the possibility to switch from antiferromagnetic (AFM) and ferromagnetic (FM) ground states (GSs) in out-stoichiometric branches of Ce2Pd2In alloys, the stability of Shastry-Sutherland (ShSu) phase of Ce2Pd2Sn as a function of Sn/In electron doping was studied. Magnetic and specific-heat measurements show that the Ce-rich compositions stabilize the FM-GS throughout the Sn/In-FM substitution, allowing to extend the formation of the ShSu phase up to its collapse in a tricritical point around ycr=0.5. On the other hand, this behavior is quite different from that reported in a recent investigation on the AFM branch where atomic disorder at intermediate Sn/In-AFM concentrations inhibits the formation of the ShSu phase.